Pendidikan Pemilih Integrated: Upaya Mengembangkan Literasi Politik Peserta Didik Sebagai Prapemilih - Hariyanti, Hariyanti; Darmawan, Cecep; Rahmat, Rahmat; Anggraeni, Leni; Rafni, Al; Suryanef, Suryanef (Universitas Negeri Malang, 2025)
This study aims to describe the weaknesses of incidental voter education in improving political literacy and the integrated voter education model as a strategy for strengthening political literacy. This study used a qualitative approach with a descriptive research type. Informants in this study include Commissioners of the Pekanbaru City General Election Commission, Election Smart House Managers, and Pancasila and Civics Education Teachers in schools. Data collection techniques were carried out through observation, interviews, and documentation studies. The data in this study are explained using the Miles and Huberman model, including data reduction, data presentation, and drawing conclusions. The results of the study indicate that incidental education has proven ineffective in improving political welfare sustainably. Voter education in schools is generally only conducted in the lead-up to elections. Integrated voter education is a solution to prepare participatory pre-voters, possess adequate political literacy, and foster a spirit of volunteerism in safeguarding democracy through collaboration between the General Election Commission and Pancasila and Civics Education Teachers.